Dryinidae of the Oriental region (Hymenoptera: Chrysidoidea) - Xu, Zaifu; Olmi, Massimo; He, Junhua (Zootaxa, 2013)
An updated revision of Oriental Dryinidae is presented. Seven subfamilies, 20 genera and 368 species are treated. Eight new species are described: Aphelopus zonalis Xu, Olmi & He, sp. nov. (China, Hainan); Anteon zoilum Xu, Olmi & He, sp. nov. (China, Yunnan), Anteon zonarium Xu, Olmi & He, sp. nov. (China, Yunnan), Anteon zopyrum Xu, Olmi & He, sp. nov. (China, Xizang), Anteon zoroastrum Xu, Olmi & He, sp. nov. (Malaysia, Malaya), Esagonatopus sinensis Xu, Olmi & He, sp. nov. (China, Yunnan), Gonatopus yunnanensis Xu, Olmi & He, sp. nov. (China, Yunnan); Ponomarenkoa ellenbergeri Olmi, Xu & He, sp. nov. (Myanmar amber). Descriptions, geographic distribution, known hosts, natural en-emies and type material of each species are presented, together with illustrations of the main morphological characters and keys to the subfamilies, genera and species. Complete lists of references concerning the Oriental Dryinidae and their hosts are given. New synonymies are proposed for Aphelopus albiclypeus Xu, He & Olmi, 1999 (=A. exnotaulices He & Xu, 2002, syn. nov.), A. orientalis Olmi, 1984 (=A. albopictoides Xu & He, 1999, syn. nov.), A. taiwanensis Olmi, 1991 (=A. compresssus Xu & Yao, 1997, syn. nov.), A. niger Xu & He, 1999 (=A. nigricornis Xu, He & Olmi, 1999, syn. nov.), A. penanganus Olmi, 1984 (=A.olmii He & Xu, 2002, syn. nov.), Anteon cacumen Xu & He, 1997 (=A. longwangshanense Xu & He, 1997, syn. nov.), A. hilare Olmi, 1984 (=A. corax Olmi, 1984, syn. nov., =A. javanum Olmi, 1984, syn. nov., =A. serratum Xu & He, 1999, syn. nov.), A. lankanum Olmi, 1984 (=A. planum Xu & He, 1999, syn. nov.), A. munitum Olmi, 1984 (=A. bauense Olmi, 1984, syn. nov.), A. parapriscum Olmi, 1991 (=A. alpinum He & Xu, 2002, syn. nov.), A. peterseni Olmi, 1984 (=A. scrupulosum He & Xu, 2002, syn. nov.), A. yuani Xu, He & Olmi, 1998 (=A. yuae He & Xu, 2002, syn. nov.), Lonchodryinus bimaculatus Xu & He, 1994 (=L. niger He & Xu, 2002, syn. nov.), L. ruficornis (Dalman, 1818) (=L. melaphelus Xu & He, 1994, syn. nov.), Dryinus indicus (Kieffer, 1914) (=Chlorodryinus koreanus Móczár, 1983, syn. nov., =Dryinus masneri Olmi, 2009, syn. nov.), D. stantoni Ashmead, 1904 (=D. undatomarginis Xu & He, 1998, syn. nov., =D. wuyishanensis He & Xu, 2002, syn. nov.), Adryinus jini Xu & Yang, 1995 (=A. platycornis Xu & He, 1995, syn. nov.), Gonatopus nigricans (R. Perkins, 1905 (=G. fulgori Nakagawa, 1906, syn. nov., =G. insulanus He & Xu, 1998, syn. nov., Pseudogonatopus sogatea Rohwer, 1920, syn. nov.; P. pusanus Olmi, 1984, syn. nov.), G. nudus (R. Perkins, 1912) (=G. yangi He & Xu, 1998, syn. nov.), G. pedestris Dalman, 1818 (=Epigonatopus sakaii Esaki & Hashimoto, 1933, syn. nov.), G. rufoniger Olmi, 1993 (=Neodryinus hishimonovorus Xu & He, 1997, syn. nov.), G. schen-klingi Strand, 1913 (=G. euscelidivorus Xu & He, 1999, syn. nov.). New combinations are proposed for Deinodryinus con-strictus (Olmi, 1998), comb. nov. (from Anteon), Dryinus asiaticus (Olmi, 1984), comb. nov. (from Alphadryinus), D. barbarus (Olmi, 1984), comb. nov. (from Mesodryinus), Gonatopus bengalensis (Olmi, 1984), comb. nov. (from Agona-topoides ), G. bicuspis (Olmi, 1993), comb. nov. (from Pseudogonatopus), G. borneanus (Olmi, 1984), comb. nov. (from Agonatopoides ); G. indicus (Olmi, 1987), comb. nov. (from Donisthorpina), G. insularis (Olmi, 1984), comb. nov. (from Agonatopoides), G. lankae (Ponomarenko, 1981), comb. nov. (from Pseudogonatopus), G. malesiae (Olmi, 1984), comb. nov. (from Pseudogonatopus), G. nepalensis (Olmi, 1986), comb. nov. (from Pseudogonatopus), G. pajanensis (Olmi, 1989), comb. nov. (from Agonatopoides), G. pyrillae (Mani, 1942), comb. nov. (from Agonatopoides), G. sarawakensis (Olmi, 1984), comb. nov. (from Pseudogonatopus), G. validus (Olmi, 1984), comb. nov. (from Pseudogonatopus).